After Postmodernism - Faye, Jan. author. aut Link
VI, 224 p.
Keywords: The philosophy of the humanistic sciences has been a blind-spot in analytic philosophy. This book argues that by adopting an appropriate pragmatic analysis of explanation and interpretation it is possible to show that scientific practice of humanistic sciences can be understood on similar lines to scientific practice of natural and social sciences.